Smart Reagent for the Recovery of Copper from PCB - Md Fazlul, Bari, Dr.; Noorzahan, Begum, Mst.; Shamsul Baharin, Jamaludin, Prof. Dr.; Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Malaysian Invention and Design Society (MINDS), 2010)
Dr. Md Fazlul Bari and his team won bronze at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.